AMBIVALENSI KEBIJAKAN PEMERINTAH ORDE BARU TENTANG GOLONGAN ETNIS TIONGHOA: SUATU TINJAUAN KEPUTUSAN PRESIDIUM KABINET NOMOR 127 TAHUN 1966 DAN INSTRUKSI PRESIDEN NOMOR 14 TAHUN 1967 - Husien Oh (Universitas Nasional, 2016)
As a complex problem, government policy towards ethnic Chinese in Indonesia during New Order government covers a variety of issues like identity, economy, politics and culture. The ethnic group that has existed in the country for hundreds of years had obtained streotyped prejudice as was reflected in policies set forth by New Order government. The paper makes an analysis of this by looking into the policy making that was taken place in mid-1960s. it is the finding of the study that the government policy towards Chinese ethnic group in mid-1960s was discriminating the group.